Psigologiese vaardighede en sportprestasie by Suid-Afrikaanse Super12-rugbyspelers - Kruger, Pieter (University of the Free State, 2003)
The aim of this study is to determine whether a relationship exists between the psychological skills and sports achievements of the South African Super12 rugby players. It is evident from literature that several researchers have already shown a correlation between psychological skills and sports achievement in various branches of sport. There is however little research available on the level of psychological skills in South African rugby players and its effect on their performance. The complete training groups of the various South African Super12 teams were evaluated during the course of the season. The players were psychometrically evaluated by means of the Athletic Coping Skills Inventory-28 (ACSI-28), Mental Skills Inventory (MSI), NEO 5-Factor Inventory and a biographical questionnaire. The results suggest that there is no particular psychological skill that can predict the above mentioned group’s rugby performance. A number of similarities between psychological skills, that is of statistical importance, were however identified. The Bulls’ team (who performed the best of all the South African Super12 teams) differed significantly from the rest of the South African teams on 4 of the 7 ACSI- 28 fields (concentration, optimal performance under pressure, self-confidence and performance motivation, as well as freedom from worry).

Die doel van hierdie studie is om te bepaal of daar ‘n verband tussen die psigologiese vaardighede en sportprestasie by die Suid-Afrikaanse Super12 rugbyspelers bestaan. Uit die literatuur is dit duidelik dat verskeie navorsers al ‘n verband tussen psigologiese vaardighede en sportprestasie in verskeie sportsoorte bewys het. Daar is egter min navorsing beskikbaar oor die vlak van psigologiese vaardighede by Suid-Afrikaanserugbyspelers en die invloed wat dit op hulle prestasie het. Die volledige oefengroepe van die onderskeie Suid-Afrikaanse Super12 spanne is tydens die verloop van die seisoen geëvalueer. Die spelers is met behulp van die Athletic Coping Skills Inventory-28 (ACSI-28), Sportvaardighede Inventaris (SVI), NEO 5-Factor Inventory en ‘n biografiese vraelys, psigometries geëvalueer. Die resultate dui daarop dat daar geen spesifieke psigologiese vaardigheid is wat rugbyprestasie by die bogenoemde groep voorspel nie. Daar is egter ‘n aantal statisties beduidende ooreenkomste tussen verskeie van die psigologiese vaardighede gevind. Die span van die Bulls (wat die beste van die Suid-Afrikaanse Super12 spanne gevaar het) het op 4 van die 7 ACSI-28 velde (konsentrasie, optimale prestasie onder druk, selfvertroue en prestasiemotivering, sowel as afwesigheid van bekommernis) beduidend van die ander spanne verskil.
Dissertation (M.A. (Clinical Psychology))--University of the Free State, 2003
Keywords: Rugby football -- Psychological aspects; Sports -- Psychological aspects; Achievement motivation; Competition (Psychology); Psychological skills; Sport achievement; Sport psychology; Rugby; Provincial rugby players; Personality and performance; Psychological preparation; Super12 rugby; Concentration; Coping with adversity; Optimal performance under pressure; Performance motivation; Self-confidence